Microdeletion 15q13.3: a locus with incomplete penetrance for autism, mental retardation, and psychiatric disorders. Issue 6 (15th March 2009) - Ben-Shachar, S; Lanpher, B; German, J R; Qasaymeh, M; Potocki, L; Nagamani, S C Sreenath; Franco, L M; Malphrus, A; Bottenfield, G W; Spence, J E; Amato, S; Rousseau, J A; et al.
Abstract : Background: Microdeletions within chromosome 15q13.3 are associated both with a recently recognised syndrome of mental retardation, seizures, and dysmorphic features, and with schizophrenia. Methods and results: Based on routine diagnostic testing of ∼8200 samples using array comparative genomic hybridisation, we identified 20 individuals (14 children and six parents in 12 families) with microdeletions of 15q13.3. Phenotypes in the children included developmental delay, mental retardation, or borderline IQ in most and autistic spectrum disorder (6/14), speech delay, aggressiveness, attention deficit hyperactivity disorder, and other behavioural problems. Both parents were available in seven families, and the deletion was de novo in one, inherited from an apparently normal parent in four, and inherited from a parent with learning disability and bipolar disorder in two families. Of the 14 children, six in five families were adopted, and DNA was available for only one of these 10 biological parents; the deletion was very likely inherited for one of these families with two affected children. Among the unavailable parents, two mothers were described as having mental retardation, another mother as having "mental illness", and one father as having schizophrenia. We hypothesise that some of the unavailable parents have the deletion. Conclusions: The occurrence of increased adoption, frequent autism, bipolar disorder, and lack of penetrance are noteworthy findings in individuals with deletion 15q13.3. A high rate of adoption may be related to the presence of the deletion in biological parents. Unconfirmed histories of antisocial behaviours in unavailable biological parents raise the concern that future research may show that deletion 15q13.3 is associated with such behaviours.